2020
DOI: 10.7717/peerj.9190
|View full text |Cite
|
Sign up to set email alerts
|

Limpet disturbance effects on barnacle recruitment are related to recruitment intensity but not recruit size

Abstract: Intertidal limpets are important grazers along rocky coastlines worldwide that not only control algae but also influence invertebrates such as common barnacles. For instance, grazing limpets ingest settling barnacle cyprid larvae (hereafter cyprids) and push cyprids and barnacle recruits off the substrate. Such limpet disturbance effects (LDEs) can limit barnacle recruitment, a key demographic variable affecting barnacle population establishment and persistence. In this study, we examined limpet (Lottia cassis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
0
0
Order By: Relevance
“…Our results show that the barnacle B. glandula has negative effects on S. granularis but positive effects on littorinids. There are many other examples of negative barnacle-limpet interactions (Dayton, 1971;Branch, 1976;Hawkins, 1983;Dungan, 1986;Santini et al, 2019;Ellrich et al, 2020), but in New South Wales, Creese (1982) showed that a small species of limpet, Patelloida latistrigata, benefits from the presence of barnacles that provide a refuge from competition with a larger species of limpet, Cellana tramoserica, which is excluded because it cannot move over and feed effectively on barnacles. Again, size matters.…”
Section: Barnacles Limpets and Periwinklesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that the barnacle B. glandula has negative effects on S. granularis but positive effects on littorinids. There are many other examples of negative barnacle-limpet interactions (Dayton, 1971;Branch, 1976;Hawkins, 1983;Dungan, 1986;Santini et al, 2019;Ellrich et al, 2020), but in New South Wales, Creese (1982) showed that a small species of limpet, Patelloida latistrigata, benefits from the presence of barnacles that provide a refuge from competition with a larger species of limpet, Cellana tramoserica, which is excluded because it cannot move over and feed effectively on barnacles. Again, size matters.…”
Section: Barnacles Limpets and Periwinklesmentioning
confidence: 99%
“…Added to this, limpets can act is 'bulldozers', reducing the abundance of small settlers of species such as barnacles (Menge et al, 2010;Ellrich et al, 2020). The situation is even more complex when other members of the community indirectly influence the outcome of interactions.…”
Section: Introductionmentioning
confidence: 99%